2019
DOI: 10.1111/jfpe.13239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drying processes on properties of polyphenol‐enriched maple sugar powders

Abstract: The aim of this research was to develop a natural food ingredient based on maple sugar powders (MSP) enriched in polyphenols. By incorporating 0.01% (wt/vol) of hot water extract (hot water extraction: 90°C and 1 hr; bark/water, 1/10 wt/vol) from sugar and red maple bark into substandard quality maple syrup, the latter was enriched by 13–20% in total phenolic content (TPC). The mixtures (syrup and extracts) were dehydrated using freeze‐drying (FD: at −36°C for 15 hr and subsequently at 30°C for 10 hr) or vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(92 reference statements)
1
2
0
Order By: Relevance
“…This is due to the long duration of exposure of the product (48 h) to the environment while at a low temperature during freeze drying, compared to the short duration of exposure of the product (several minutes) during drum drying but at a high temperature. These results agree with the observation by Bhatta et al [36] who reported lower retention of total polyphenol content in freeze-dried maple sugar than that of vacuum double-drum-dried sugar.…”
Section: Effect Of Processing On Measured Contents Of Total Soluble Phenolicssupporting
confidence: 93%
“…This is due to the long duration of exposure of the product (48 h) to the environment while at a low temperature during freeze drying, compared to the short duration of exposure of the product (several minutes) during drum drying but at a high temperature. These results agree with the observation by Bhatta et al [36] who reported lower retention of total polyphenol content in freeze-dried maple sugar than that of vacuum double-drum-dried sugar.…”
Section: Effect Of Processing On Measured Contents Of Total Soluble Phenolicssupporting
confidence: 93%
“…One such nontraditional plant source food is maple syrup. Maple syrup is composed of a mixture of sugars (66% sucrose, 0.4% glucose, and 0.5% fructose), minerals and water, and traces of organic acids, proteins, and polyphenols [66]. Bhatta et al [67] studied the drying of maple syrup to produce a maple sugar powder.…”
Section: Nontraditional Sourcementioning
confidence: 99%
“…This is lower than the PPAQ averages of 1183 µg/g and a range of 488-2124 µg/g based on the analysis of 135 dark, robust taste syrups. Gallic acid equivalent values may reach 8040 µg/g for very dark maple syrup [31], nearly four times the maximum reported by the PPAQ. Such variations have been attributed to the well-known limitation of the Folin-Ciocalteu assay [44,45], which is an indirect method that can be influenced by non-phenolic compounds (e.g., sugars, organic acids) [46].…”
Section: Total Polyphenol Contentmentioning
confidence: 64%
“…Total polyphenol content was determined using a Folin-Ciocalteu assay [30], modified for use in 96-well microplates [31] with slight modifications. The first three columns were loaded with 0, 10, 20, 30, 40, 50, 60 or 70 µL of a gallic acid standard (50 µg/mL) and then adjusted accordingly with nanopure water to obtain a total volume of 180 µL.…”
Section: Total Polyphenol Contentmentioning
confidence: 99%